Bibliometric Analysis of Demographic Research Related to Fertility Using VOSviewer - Aryati, Seri; Sukamdi, Sukamdi; Listyaningsih, Umi (Center for Populatioan and Policy Studies Universitas Gadjah Mada, 2025)
Fertility is a critical aspect of demographic and health studies, directly influencing population growth and public health. This study employs a bibliometric approach to analyze fertility research from 2000 to 2020, utilizing VOSviewer software to visualize the relationships between key topics in the field. Through an extensive analysis of scientific literature from the Scopus database, the study identifies key research themes, such as low fertility, health surveys, reproductive technology, and the impact of the COVID-19 pandemic. The findings reveal that health surveys have consistently been a central focus in fertility research, providing essential data on fertility trends and their implications. Additionally, the emergence of reproductive technologies, such as In Vitro Fertilization (IVF), has been instrumental in addressing infertility, thus influencing fertility decisions globally. The study also highlights how the COVID-19 pandemic has shifted fertility behaviours, with many couples delaying childbearing due to economic and health uncertainties. The interconnectedness of topics like parenthood, fertility intentions, and socio-economic factors underscores the importance of a multidisciplinary approach to fertility research. This analysis offers valuable insights for policymakers and researchers in developing strategies to address future demographic challenges and fertility-related issues.